2019
DOI: 10.1186/s12933-019-0933-y
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of the impact of alpha-glucosidase inhibitors on incident diabetes and cardiovascular outcomes

Abstract: Background Alpha-glucosidase inhibitors (AGIs) have been shown to reduce incident type 2 diabetes but their impact on cardiovascular (CV) disease remains controversial. We sought to identify the overall impact of AGIs with respect to incident type 2 diabetes in individuals with impaired glucose tolerance (IGT), and CV outcomes in those with IGT or type 2 diabetes. Methods We used PubMed and SCOPUS to identify randomized controlled tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…We observed increased risk of repeated PCI among patients treated with insulin, SU, meglitinide and AGI. Coleman et al [ 31 ] suggested no overall impact of AGI on CV outcomes in a meta-analysis and concluded that AGIs would rather not be indicated for CV secondary prevention. There are ongoing debates regarding the use of insulin in patients at high risk of CAD.…”
Section: Discussionmentioning
confidence: 99%
“…We observed increased risk of repeated PCI among patients treated with insulin, SU, meglitinide and AGI. Coleman et al [ 31 ] suggested no overall impact of AGI on CV outcomes in a meta-analysis and concluded that AGIs would rather not be indicated for CV secondary prevention. There are ongoing debates regarding the use of insulin in patients at high risk of CAD.…”
Section: Discussionmentioning
confidence: 99%
“…When used as monotherapy in patients with type 2 diabetes, the average reduction in HbA1c is 0.8% without risk of hypoglycemia [86]. While an earlier study suggested that acarbose may reduce the incidence of cardiovascular events [87], a recent meta-analysis comparing AGIs with placebo for cardiovascular outcomes suggested a neutral effect [88]. These agents can cause significant gastrointestinal adverse effects, including flatulence, diarrhea, and abdominal pain, resulting in poor adherence [89].…”
Section: α-Glucosidasementioning
confidence: 99%
“…45 To summarize, Table 6 provides an overview of the efficacy, CV safety and side effects of various classes of OADs. 47 Neutral effect on CV outcomes 48 Flatulence, diarrhea 49 Main for PPG, low risk of hypoglycemia, CV safety to be evaluated 48,50…”
Section: Sglt2 Inhibitorsmentioning
confidence: 99%